Impaired adaptive immune response in COVID‐19 convalescent patients with hematological malignancies. (30th December 2022) - Kalicińska, Elżbieta; Szymczak, Donata; Andrasiak, Iga; Milanowska, Aneta; Kiraga, Aleksandra; Majeranowski, Alan; Jabłonowska, Paula; Rybka, Justyna; Maciej, Zaucha; Wróbel, Tomasz
Abstract: Objectives: The immune dysregulation during SARS‐CoV‐2 has the potential to worsen immune homeostasis after recovery. Patients with hematological malignancies with COVID‐19 have changes both in the innate and adaptive immune responses. Little is known about the severity of immune dysfunction following recovery from COVID‐19 in hematological patients. Methods: Here, we performed a comprehensive analysis of the lymphocyte subsets in peripheral blood mononuclear cells by FACS Canto II in 55 patients, including 42 with hematological malignancies 4–6 weeks after COVID‐19. Results: Hematological COVID‐19 convalescents had deep reduction in CD3+ T cells, including helper T cells (CD3 + CD4+), naïve helper T cells (CD3 + CD4 + CD45RA+), and memory CD4+ T cells among with extremely low levels of Treg cells and decreased expression of both TCRα/β and TCRγ/δ. Severe immune dysregulation in hematological convalescents was expressed by increased activation of T lymphocytes, both as elevated levels of activated T cells (CD3 + HLA‐DR+) and activated cytotoxic T cells (CD3 + CD8 + HLA‐DR+). Conclusions: Our findings showed a profound impairment of the adaptive immune response in hematological convalescents which might be a result of persistent activation of T cells. Convalescents with lymphoid malignancies showed more pronounced depletion of key T lymphocytes subpopulations in creating an effective adaptive response and immune memory.